Analysis of Fire Emergency Response Readiness at Hospital Building: Fire Emergency Response Readiness Assessment Tools Method - Dwi Septiana; Fatma Lestari (Journal of Social Research, 2025)
Fire safety in healthcare facilities is a crucial aspect of risk management, especially in hospitals that have a high level of complexity in patient evacuation and medical asset protection. Therefore, an evaluation of fire emergency response readiness is needed to ensure the effectiveness of the mitigation system implemented. This study used the Fire Emergency Response Readiness Assessment Tools (FERRAT) form to assess the readiness of fire safety management in hospitals. Data was collected through direct observation methods, in-depth interviews with fire safety teams, and analysis of policy documents and emergency response procedures. The study showed that the overall fire safety readiness of the elements that had reached an average of <90% with an overall value of 91.28%. This achievement indicates that risks in hospital operational activities have been managed safely, so that mitigation of patient safety in fire emergency conditions can be carried out optimally. Although several aspects still require significant improvement. The main weaknesses were identified in the frequency of staff training, the maintenance of fire protection systems, and the effectiveness of coordination between units in dealing with emergency situations. this study may support hospitals in independently evaluating in conducting independent evaluations and immediately implementing improvements related to risk-based system design, adequacy according to potential fire risks, and ensuring that emergency response equipment is always in a ready and optimal condition for operation.